Comparative study of Software-Defined Networking (SDN) traffic controllers - Pereira, Goncalo (2019)
The SDN (Software-defined Nettworking) has introduced a new control paradigm in network infrastructures, thus having a great impact not only on the operation of the network itself, but also on supporting all the development carried out around them (e.g. network and distributed services, Internet applications, etc.). In this context, and in order to assist researchers and professionals in these areas, this article presents a comparative study among several SDN controllers in the market. In a first phase, a more general analysis is made on several controllers, highlighting their general characteristics and the areas where some scientific works were developed using each of the controllers. After that, a selection of some controllers is made, and some illustrative microprojects were implemented, allowing to obtain a comparative analysis of the learning curves and some of the main APIs supported by each SDN controller.